The effect of plant extracts in human prostate cells - Gonçalves, Sara Isabel Hilário (2020)
Prostate cancer is one of the most frequent malignancies diagnosed in men and the second cause of cancer-related deaths in Western countries. Despite several developments in the last decades, better approaches are still needed for the treatment and management of this pathology. Natural products have been used as a therapeutic resource since ancient times. Over the years there has been increasing evidence that medicinal plants play a crucial role in the prevention and mitigation of different human diseases. Polyphenols are a large class of chemicals found in plants that have attracted much attention in the last decades due to their antiproliferative properties and antioxidant effects, which has increased the interest on the investigation of its applicability controlling the growth of cancer cells. Much less is known considering the effects of polyphenols controlling other specific features of cancer cells, as their ability to suppression of highly glycolytic metabolism and the reprogram metabolism. Crataegus monogyna and Arbutus unedo are examples of plants rich in phenolic compounds. The C. monogyna, “pirliteiro”, is a species of the class Mognoliopsida, order Rosales, family Rosaceae, widely distributed in the Iberian Peninsula, Western and Central Europe and North of Africa. This plant has been studied due to its pharmacological interest, having various benefits in hypertension, heart and digestive disorders. The A. unedo, “medronheiro”, is a species of the class Mognoliopsida, order Ericales and family Rosaceae. It grows spontaneously around the Mediterranean basin, as well as, in other regions with hot summers and mild rainy winters. This plant has been long used in folk medicine, on traditional remedies, due to its several health-promoting characteristics, for treatment of gastrointestinal and urological problems, hypertension, cardiac diseases, and diabetes and as antiinflammatory agent, among other interesting properties. The present study investigated the activity of C. monogyna and A. unedo extracts controlling human non-neoplastic (PNT1A) and neoplastic (LNCaP and PC3) prostate cells growth. Methanolic extracts of dry leaves were obtained by ultrasound-assisted extraction. PNT1A, LNCaP and PC3 cells were treated with different concentrations of the purified extracts (0, 10, 50, 100, 200, 500 and 1000 µg/ml) for 24, 48, and 72 h. Cell viability at different experimental conditions was determined by the MTT assay. Integrating the results of cell viability obtained for the three prostate cell lines under study in the presence of both plant extracts, the 200 µg/ml concentration and the incubation time of 72 h were selected for the subsequent analysis of apoptosis and metabolism. The alteration on the protein expression of key apoptosis and metabolic regulators was analyzed using the Western Blot. The glucose consumption, lactate production, activity of lactate dehydrogenase (LDH) and activity of Caspase-3 were evaluated by biochemical assays using specific kits and subsequent spectrophotometric analysis. Distinct responses were observed in non-neoplastic (PNT1A) and neoplastic (LNCap and PC3) prostate cells upon exposure to C. monogyna and A. unedo extracts. For both extracts, the viability of LNCaP and PC3 cells started to decrease from 100 and 200 µg/ml on, for 72 h of treatment. PNT1A cells proliferation was significantly different, starting only at a concentration of 500 µg/ml. Nevertheless, the administration of both plants extracts decreased prostate cell proliferation. Considering cell-death, A. unedo extracts increased the apoptotic rate of PNT1A cells, which was underpinned by the altered expression of key apoptosis regulators. An effect not observed in the apoptotic rate of the neoplastic LNCaP and PC3 cells. LNCaP cells treated by C. monogyna extracts markedly displayed a suppression of glycolytic metabolism with decreased LDH activity and lactate production, which was accompanied by altered expression/activity of glycolytic transporters and enzymes. Curiously, PC3 cells had an overall down-regulation of apoptotic and metabolic activity in the presence of C. monogyna and A. unedo extracts, despite the decreased proliferation. The present findings indicate that C. monogyna and A. unedo extracts may have beneficial effects on neoplastic and nonneoplastic prostate cells, diminishing proliferation and controlling the apoptotic and glycolytic pathways. These effects were more pronounced in the case of the androgensensitive LNCaP cells.